The Effects of Pre-Transplant HDL Cholesterol Levels on Survival in Patients with Liver Transplantation - Akbulut, Sami; Kayaalp, Cuneyt; Yilmaz, Mehmet; Karabulut, Kagan; Karabulut, Koray; Sakcak, Ibrahim; Yilmaz, Sezai (Wiley-Blackwell, 2012)
[Abstract Not Available]
18th Annual International Congress on ILTS -- MAY 16-19, 2012 -- San Francisco, CA